b revered meditation master explorers two of the world's great contemplative traditions /c - Hanh, Thich Nhat. (b, 1995)
Buddha and Christ each left a legacy of teachings and practices that have shaped the lives of billions of people. If they were to meet today, what would each think of the other's spiritual views and practices? This book explores how the two traditions meet and awakens an understanding of both.
Keywords: v; Jesus Christ; Christianity and other religions -- Buddhism